The determinants of bank’s credit risk: ---An empirical study of UK commercial banks - Xu, zeyang (2019)
Credit risk is one of the important risks for the banking industry. The main purpose of this thesis is to explore the determinants of the banking credit risks for the UK commercial banks during the period of 2013-2018. This thesis used the ratio of non-performing loans (NPLs) to represent the probability of defaults. It took both microeconomic and macroeconomic determinants into consideration. In addition, the panel data approach was applied to examine the relationship between NPLs and its determinants. According to the final results, the credit risk of UK commercial banks from 2013-2018 has been mainly affected by microeconomic factors, especially the determinants of Loan loss provisions and the bank size (LNTA). The results also indicate that the macroeconomic determinants seem have no significant correlations with the credit risk. It probably because as the developed country, the economy environment of UK is relatively stable, especially after the 2008 financial subprime crisis, although it has been affected by the ‘Brexit’ after 2016.